Unconventional meiotic process of spermatocytes in male Cyprinus carpio - La Zhu; Wangchao He; Hui Zhang; Yu Sun; Qi Li; Luojing Zhou; Shurun Zhu; Min Tao; Yi Zhou; Rurong Zhao; Kaikun Luo; Chenchen Tang; et al. (Reproduction and Breeding, 2021)
The spermatogenesis of fish remained unclear about the cytological process, especially on the meiotic process of spermatocytes after meiosis I. In the present study, microstructure and ultrastructure of spermatogenesis in Cyprinus carpio (abbreviated CC) were studied, the meiosis process was traced by chromosomal observation and the corresponding immunohistochemical staining of testis where spermatocytes at different stages were distinguished. Results firstly described the telomere-led bouquet configuration of prophase I-stage cells in fish, which ensure the normal chromosomal behavior just like in other eukaryotes. Compared to the canonical meiotic process, the spermatocytes at leptotene, zygotene, pachytene, diplotene and diakinesis stages in CC were normal and also proceeded metaphase I interacting with the meiotic spindle as a unit, while the subsequently meiosis II in CC demonstrated contradicted findings in most organisms, in which no obvious spindle-dependent sister chromatids aligning and segregating could be observed, but some circular condensed nucleus structures. Furthermore, protein antibody of RAD51, DMC1, RNA-Pol II CTD P–S5, H3K36me3 were used respectively as probes, marked initially between the primary spermatocytes at prophase I and metaphase I stage, and between the spermatids and spermatozoa. The systematical study in cytological characteristics of the whole meiotic process in fish spermatogenesis in this paper, provide a standard reference for fish meiosis, which can be of great significance in the practice of fish genetics and breeding.